2002
DOI: 10.1073/pnas.122126299
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the vitamin D-binding protein and its complex with actin: Structural basis of the actin-scavenger system

Abstract: Actin is the most abundant protein in eukaryotic cells, but its release from cells into blood vessels can be lethal, being associated with clinical situations including hepatic necrosis and septic shock. A homeostatic mechanism, termed the actin-scavenger system, is responsible for the depolymerization and removal of actin from the circulation. During the first phase of this mechanism, gelsolin severs the actin filaments. In the second phase, the vitamin Dbinding protein (DBP) traps the actin monomers, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
124
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 38 publications
3
124
0
2
Order By: Relevance
“…Distinct binding regions within the 458 amino acid sequence of DBP have been identified. Analysis of the crystal structure of DBP (bound to either vitamin D 3 or actin) has confirmed previous studies that the vitamin D sterol binding segment resides in the N-terminal domain (amino acids 35-49) (Haddad et al, 1992;Swamy et al, 1997), and also revealed that actin interacts with distinct amino acid sequences in all three DBP domains Otterbein et al, 2002;Swamy et al, 2002;Verboven et al, 2002). Recently, our lab has identified a C5a chemotactic cofactor region in the N-terminal domain (amino acids 130-149), a sequence distinct from either the vitamin D or G-actin binding regions (Zhang and Kew, 2004).…”
Section: Introductionsupporting
confidence: 81%
“…Distinct binding regions within the 458 amino acid sequence of DBP have been identified. Analysis of the crystal structure of DBP (bound to either vitamin D 3 or actin) has confirmed previous studies that the vitamin D sterol binding segment resides in the N-terminal domain (amino acids 35-49) (Haddad et al, 1992;Swamy et al, 1997), and also revealed that actin interacts with distinct amino acid sequences in all three DBP domains Otterbein et al, 2002;Swamy et al, 2002;Verboven et al, 2002). Recently, our lab has identified a C5a chemotactic cofactor region in the N-terminal domain (amino acids 130-149), a sequence distinct from either the vitamin D or G-actin binding regions (Zhang and Kew, 2004).…”
Section: Introductionsupporting
confidence: 81%
“…Actin's natural tendency to polymerize constitutes an obstacle to crystallization. Different approaches have been used to overcome this problem, including the crystallization of complexes of actin with actin-binding proteins (ABPs) (20,(22)(23)(24)(25)(26) and toxins (27), and blocking actin polymerization by mutagenesis (28) or chemical cross-linking (29). We chose to attempt Author contributions: E.D.K.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of actin phosphorylation, which is very low in growing vegetative cells, begins to increase [12][13][14][15][16][17][18][19][20][21][22][23][24] h into the developmental cycle, reaching Ϸ50% of the total actin at Ϸ36 h (9)(10)(11). At this high level of actin phosphorylation, the spores of the mature fruiting bodies remain viable for Ϸ20 days, at which time viability and actin phosphorylation levels both decrease, disappearing entirely by Ϸ30 days.…”
mentioning
confidence: 99%
“…Toxofilin, like gelsolin (21), vitamin D-binding protein (22), formin (23), WH2 (15), and ciboulot (24), presents a helix (helix 3) that binds in the cleft between actin subdomains 1 and 3 (13). Toxofilin 69-196 helix 3 superimposes particularly well with the helix of WH2 (Fig.…”
Section: Discussionmentioning
confidence: 99%